Senescence State in Mesenchymal Stem Cells at Low Passages: Implications in Clinical Use - Alves-Paiva, Raquel M.; Nascimento, Sabrina do; De Oliveira, Denise; Coa, Larissa; Alvarez, Kelen; Hamerschlak, Nelson; Okamoto, Oswaldo Keith; Marti, Luciana C.; Kondo, Andrea T.; Kutner, Jose Mauro; Bortolini, Maria Augusta Tezelli; Castro, Rodrigo; et al. (Frontiers in Cell and Developmental Biology, 2022)
Mesenchymal stem cells (MSCs) are multipotent cells found in various tissues and are easily cultivated. For use in clinical protocols, MSCs must be expanded to obtain an adequate number of cells, but a senescence state may be instituted after some passages, reducing their replicative potential. In this study, we report a case where MSC derived from an elderly donor acquired a senescence state after three passages. Bone marrow was aspirated from a female patient submitted to a cell therapy for incontinency urinary protocol; MSCs were cultivated with DMEM low glucose, supplemented with 10% autologous serum (AS) plus 1% L-Glutamine and 1% Antibiotic/Antimycotic. Senescence analysis was performed by β-Galactosidase staining after 24h and 48h. Controls were established using BM-MSC from healthy donors and used for senescence and gene expression assays; Gene expression was performed using RT-PCR for pluripotency genes, such as SOX2, POU5F1, NANOG, and KLF4. MSCs telomere length was measured by Southern Blotting technique and MSCs were also analyzed for their capacity to differentiate into adipocytes, chondrocytes and osteocytes. The patient’s MSCs expansion using AS displayed an early senescence state. In order to understand the AS role in senescence, MSCs were then submitted to two different culture conditions: 1) with AS or 2) FBS supplementation. Senescence state was assessed after 24h and no statistical differences were observed between the 2 conditions. However, patient’s cells cultured with AS displayed higher number of senescence cells in comparison to FBS media after 48h (p = 0.0018). Gene expression was performed in both conditions; increased expression of KLF4 was observed in the patient’s cells in comparison to healthy controls (p = 0.0016); reduced gene expression was observed for NANOG (p = 0.0016) and SOX2 (p = 0.0014) genes. Telomere length from the patient’s cells was shorter when compared to healthy donor and when compared to a patient with similar age. Osteocyte differentiation seemed to be more diffuse when compared to the healthy and patient from similar age. MSCs could enter a senescence state during expansion in early passages and can impact MSC quality for clinical applications, reducing their efficacy when administered.